Book Review: Working towards Equity by Dustin Galer - Vaccaro, Angelina (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2020)
Book Review of Working towards Equity: Disability Rights Activism and Employment in Late Twentieth-Century Canada. By Dustin Galer. University of Toronto Press, 2018. 309 pages. ISBN 978148750131